Supply chain management and logistics in emerging markets : selected papers from the 2018 MIT SCALE Latin America Conference - Yoshizaki, Hugo Tsugunobu Yoshida,; Velázquez-Martínez, Josué Cuauhtémoc,; Mejia-Argueta, Christopher, (Emerald Publishing Limited, 2020)
In April 2018 more than 150 researchers from 16 different countries convened at MIT for the second SCALE Latin American Conference on Supply Chain Management and Logistics (SCM&L). This edited book presents 18 papers on SCML in Latin America which emerged from this conference. As a region with more than 640 million people, and an economy that grows faster than those of developed regions, Latin America is the subject of large infrastructure projects and heightened interest from multinational companies. With contributors spanning eleven different countries, and comprising MIT faculty and researchers, and academics from prestigious Latin American institutions, this collection covers a variety of relevant topics in SCM&L for the region, and also addresses its lack of cases and applied examples. With cases from Argentina, Ecuador, Mexico, and Paraguay, this book breaks fresh ground by looking at risk analysis, and small firms supply chain management. Making a solid contribution to the regional needs for SCM&L literature for education, research, and practice, this book is relevant to researchers and professionals living and operating in the region, as well as in developing economies beyond.